Análise dos determinantes da duração e abandono em contratos de planos odontológicos individuais e familiares - Silva, Rivanio Paulino da (2014)
This research analyzes the determinants of the duration and abandonment of dental plan contracts unilaterally by the beneficiaries and, therefore, had made available a database with 36 (thirty six) variables and 128,366 (one hundred and twenty eight thousand, three hundred and sixty-six) who had their contracts terminated recorded between the years 2008-2013. Through preliminary tests, it can be inferred that there is a dishonest relationship of beneficiaries who could hire the plans , use the services and subsequently fails to meet its obligations, since more than 80% (eighty percent), abandoned the plans after pay more than 24 (twenty four) installments without using any procedure , even a prevention. An econometric model of logistic regression allowed us to infer that the beneficiaries of females who do not pay with billets and did not their contracts through Call Center has less chance of abandonment and , in turn , men who pay with billets and sale was through the Call Center are more likely to abandon the contract.